Effect of Added Urea Foliar Spray and Leaf Clipping on Growth and Yield Response of Mungbean (Bangladesh Agronomy Journal, 2023)
An experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka, during March to May 2018 to study the impact of added urea foliar spray and leaf clipping on growth and yield of mungbean. The experiment was laid out in Split-plot Design with three replications and composed of four levels of urea foliar spray viz. F0 = Recommended Fertilizer (RF) + No Foliar Spray (FS), F1 = RF + 1% Urea FS at Flower Initiation (FI), F2 = RF + 2% Urea FS at FI, F3 = RF + 3% Urea FS at FI and four levels of Leaf clipping viz. C0 = No leaf clipping, C1 = Clipping 1 basal leaf, C 2 = Clipping 2 basal leaves, C3= Clipping total apical leaves having no inflorescence. Results indicated that foliar spray and leaf clipping had significant effect on most of the growth and yield contributing parameters. In case of foliar spray of urea, the maximum plant height, nodules plant-1, highest above ground dry matter plant-1, pods plant-1, pod length, seeds pod-1, 1000 seed weight, seed yield, stover yield and biological yield were recorded from F0. In case of leaf clipping, all growth and yield attributes were recorded highest from C1. Regarding combined effect, the highest growth and yield parameters were recorded from the treatment combination of F0C1. So, F0 along with C1 is suggested for yield improvement in mungbean cultivation.Bangladesh Agron. J. 2022, 25(2): 57-65